Reduction of the Toxicity of CPAs is Without Compromising the Cryoprotection in Sea Urchin Eggs (Part 2) - Rodríguez-Gavieiro, Uxía; Campos, Sara; Pereira-Pinto, Estefanía; Paredes, Estefanía (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):290